Portraying Blindness: Nineteenth-Century Images of Tactile Reading - Heather Tilley (Disability Studies Quarterly, 2018)
In this article, I examine images of blind people in nineteenth-century Europe and America, and question the ways in which shifting sensory hierarchies constituted the representation of blindness in this period. I focus particularly on images of blind people reading by touch, an activity that became a public symbol of the various initiatives and advancements in education and training that were celebrated by both blind and sighted spokespeople. My discussion is structured around institutionally- and individually-commissioned portraits and I distinguish between the different agendas shaping representations of blind people. These include instances where blind people's achievements are problematically displayed for sighted benefactors; as well as examples of blind people determining the compositional form and modes of circulation of their likenesses thus altering "key directions in figurative possibilities" (Snyder 173). Moreover, the portraits I consider demonstrate the multisensory status of images, alerting us to a nineteenth-century aesthetic that was shaped by touch as well as vision. I draw on sensory culture theory to argue that attending to the experience and representation of the haptic in the circulation of visual images of blind people signals a participatory beholding, via which blindness is creatively – rather than critically – engaged.